Mechanical valve replacement without anticoagulation: a case report. Issue 1 (15th January 2021) - Wang, Yapeng; Lin, Min; Ge, Shenglin; Feng, Junbo
Abstract: Background: For patients who undergo mechanical valve replacement, the greatest disadvantage is that they require long-term or permanent use of anticoagulant therapy to prevent thromboembolism. To date, mechanical valve replacement without anticoagulation has been published in the literature. Case summary: We present the case of a 75-year-old female who underwent mechanical mitral valve replacement (MVR) on mid- June, 2007. However, this patient had not been taking anticoagulant medication since she experienced warfarin overdose in the first month after the operation. She had been well without using any anticoagulation, and there were no complications of the mechanical valve. Discussion: There was no thrombosis for such a long period of time because she suffered from FX deficiency. To the best of our knowledge, she may be the only patient who has been well without any anticoagulation since not taking warfarin 12 years ago.